Biomimetic polysaccharide/bioactive glass nanoparticles multilayer membranes for guided tissue regeneration. Issue 79 (11th August 2016) - Rodrigues, José R.; Alves, Natália M.; Mano, João F.
Abstract : Freestanding multilayered membranes, produced with chitosan, hyaluronic acid and bioactive glass nanoparticles, were shown to behave differently based on composition. Abstract : Nowadays, guided tissue regeneration (GTR) research is centred in the development of composite bioabsorbable membranes with enhanced bioactivity and with processing controlled at the nanoscale. Inspired by this new focus of GTR research and also by nacre structure, layered freestanding membranes were produced using the Layer-by-Layer (LbL) deposition technique, combining chitosan (CHI), hyaluronic acid (HA) and bioactive glass nanoparticles (BGNPs). It is expected that the combination of these materials processed by this particular technique will result in nanostructured membranes with enhanced mechanical performance as well as improved bioactivity. Moreover, the effect of the modification of HA with catechol groups (HAD) on the adhesive properties of the membranes was also analysed. The results showed that it was possible to produce biomimetic membranes with different surface properties, improved adhesive strength and the ability to induce the formation of apatite, necessary for the formation of new bone. It was also possible to control the BGNPs content of the membranes by use of HAD instead of unmodified HA and changing the number of BGNPs' deposition steps. Moreover, it was shown that membranes with different concentrations of BGNPs possess different mechanical performance, swelling properties and degradation behaviour, which indicates the possibility to tune the membranes' properties by controlling the deposition of BGNPs onto the membranes.